Spring cookbook : over 100 hands-on recipes to build Spring web applications easily and efficiently - Jaglale, Jérôme (Quick answers to common problems., 2015)
This book is for you if you have some experience with Java and web development (not necessarily in Java) and want to become proficient quickly with Spring.